2011
DOI: 10.1039/c1ob05223c
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination and ortho-acetoxylation of 2-arylbenzoxazoles

Abstract: Efficient and facile catalytic protocols for chlorination and ligand-directed ortho-acetoxylation of 2-arylbenzoxazoles have been developed. The chlorination is not a ligand-directed ortho-functionalization, but an electrophilic substitution process in the benzo ring of the benzoxazole moiety. Meanwhile, the acetoxylation exhibited high regioselectivity for the substrates containing a meta-substituent and occurred at the less sterically hindered ortho-C-H bond of the directing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…From these reactions, we can know that a was the coupled product and a lot of a can be observed during the dehydrogenation of benzyl alcohol. But all the yield was based on o-nitrophenols, the possible measured products were c, d, e, f and g. And we did not observed the reaction (5) and (6) under catalysis of heterogeneous Au catalysts. When employing heterogeneous Pd catalysts, we can observe the reaction (5).…”
Section: General Procedures For Synthesis Of Benzoxazoles and Benzimidmentioning
confidence: 68%
“…From these reactions, we can know that a was the coupled product and a lot of a can be observed during the dehydrogenation of benzyl alcohol. But all the yield was based on o-nitrophenols, the possible measured products were c, d, e, f and g. And we did not observed the reaction (5) and (6) under catalysis of heterogeneous Au catalysts. When employing heterogeneous Pd catalysts, we can observe the reaction (5).…”
Section: General Procedures For Synthesis Of Benzoxazoles and Benzimidmentioning
confidence: 68%
“…Acetoxylation of 51 , each with two potentially active positions for palladation and subsequent C–O bond formation, gave only monosubstituted products 52 , determined by HMBC (heteronuclear multiple bond correlation) . Ac 2 O plays an important role in the oxidative addition step (Scheme ).…”
Section: Intermolecular Acyloxylationmentioning
confidence: 99%
“…Acetoxylation of 51, each with two potentially active positions for palladation and subsequent C-O bond formation, gave only monosubstituted products 52, determined by HMBC (heteronuclear multiple bond correlation). [42] Ac 2 O plays an important role in the oxidative addition step (Scheme 16). Unlike that of oxygen, the presence of sulfur in heterocyclic cores 53 led to the mono-and disubstituted products in Pdcatalyzed acetoxylation (Scheme 17).…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that the ultrasound irradiation was an efficient method for the one-pot synthesis of 2-substituted benzoxazoles. The structures of products were completely characterized by spectroscopic data such as IR, 1 H NMR, 13 C NMR and melting point and they were consistent with those of authentic samples [14,[38][39][40][41][42].…”
Section: Synthesis Of 2-aryl Substituted Benzoxazolesmentioning
confidence: 81%